1997
DOI: 10.1080/15216549700201401
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of A manganese‐rich particle in lysosome of rat pancreas due to excess manganese treatment

Abstract: Manganese (Mn) accumulates at a higher level in the pancreas than in any other organs when excess Mn is administered to the rat. The present study is carded out to analyze the intracellular localization of Mn existed in the pancreatic cell of Mn‐treated rats. Transmission electron microscope and X‐ray micro‐analysis connected with a rapid freezing fixation technique showed that a large amount of Mn was localized in tysosomal particles of the pancreatic cell of Mn‐treated rats. The Mn‐rich particles disappeared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Nonetheless, only a handful of studies so far have investigated distribution of the element in the organ with no distinction between exocrine and endocrine components. Mn was found to accumulate primarily in lysosomes where it is bound to pro‐carboxypeptidase B, a zymogen found in the exocrine portion of the pancreas . Two studies on isolated rodent pancreatic islets used Mn to study Ca handling in β ‐cells and found a significant Mn uptake following glucose stimulation in all fractions, except for microsomes, with the mitochondrial fraction having the highest percentage increase .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, only a handful of studies so far have investigated distribution of the element in the organ with no distinction between exocrine and endocrine components. Mn was found to accumulate primarily in lysosomes where it is bound to pro‐carboxypeptidase B, a zymogen found in the exocrine portion of the pancreas . Two studies on isolated rodent pancreatic islets used Mn to study Ca handling in β ‐cells and found a significant Mn uptake following glucose stimulation in all fractions, except for microsomes, with the mitochondrial fraction having the highest percentage increase .…”
Section: Discussionmentioning
confidence: 99%
“…When considering the in vivo application of MEMRI to pancreatic islets, the organ anatomy is a further complication. In the pancreas the β ‐cell‐rich endocrine tissue is highly dispersed within the acinar exocrine tissue, which has high affinity for Mn . In rodents, the acquisition of good high‐resolution images of the pancreas that allow discernment of the two tissue components is hindered by respiratory motion and by low tissue density.…”
Section: Discussionmentioning
confidence: 99%
“…Lysosomes regulate cellular micro‐environmental homeostasis by trans‐lysosomal membrane transports and fusion with other subcellular structures. Interestingly, while Mn 2+ entry into and exit out of lysosomes require cross‐membrane transport machineries, lysosomal Mn 2+ is exported out of cells with vesicular fusions with plasma membrane, and while lysosomal Mn 2+ is transported into the cytoplasm with concentration difference, Mn 2+ is transported into lysosome from the cytoplasm by inverse concentration difference …”
Section: Lysosomal Handling Of Trace Metals and Lipidsmentioning
confidence: 99%